Implementasi Strategi Penggunaan Media Gambar Pada Mata Pelajaran Al-Qur’an Hadits di SMP IT Ruhul Jadid - Khair, Muhammad Ikhsanul Khair; Rizka Harfiani (LP. Ma'arif Janggan Magetan, 2024)
This study aims to analyze the implementation of the use of image media as an additional method in improving student learning outcomes in the subject of the Qur'an and Hadith at SMP IT Ruhul Jadid. The method used is a qualitative descriptive approach by collecting data through observation, interviews, documentation of the implementation of image media in the learning process. The results of the study on the implementation of the use of image media show that the use of image media has succeeded in making it easier for students to understand the verses of the Qur'an, involving students in learning, and creating a dynamic and interactive learning environment. In conclusion, the implementation of image media as an additional strategy in the quality of learning the Qur'an and Hadith at SMP IT Ruhul Jadid, strengthens the spiritual and social dimensions of students through a holistic educational approach.